Availability of pediatric cardiovascular surgeons in Peru in 2019 - Pinto-Salinas, Miguel (2020)
Objective: to describe availability of pediatric cardiovascular surgeons and to identify factors influencing accreditation for this specialty in Peru. Materials and methods: this is a cross-sectional and descriptive study. A discriminating exponential snowball sampling procedure was performed in pediatric cardiovascular surgeons working in the Peruvian National Cardiovascular Institute. This was carried out in April 2019. Their participation was requested and virtual surveys were carried out. Data collected from closed questions were processed using descriptive statistics. Data from open questions were processed on the basis of their systematization, order, and relationship, so conclusions could be drawn. Results: twenty surgeons were surveyed. Of them, 5 reported having had training for their subspecialty, and they declared their main motivation was having undergone a training period during pregraduate or specialty studies, as well as their interest in surgery. Three accredited subspecialists declared they wanted to formalize their practice in Peru, and the other two declared not having formalized their training because of lack of time. Also, eleven surgeons expressed their desire for achieving accreditation. On the other hand, seventeen surveyed professionals declared that Peru requires more subspecialists. Conclusion: there is lack of pediatric cardiovascular surgeons in Peru; so increasing posts for such subspecialists is necessary, and also there is an urgent need for increasing, improving, and articulating specialized centers.